Preference for utilization of drug information sources among postgraduate medical residents - Gandhi, Kedar; Jadhav, Pradeep R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug use information is vital for ensuring rationale and safe drug therapy. Physician across the globe use different sources of drug information during their routine practice. Postgraduate residents are in their interim-phase of education, research and clinical exposure. They are exposed to vast array of authentic and non-authentic drug information due to technology advancements and interaction with peers and medical representatives. There exists paucity in literature on their preference and drug information pattern. Therefore, this study was conducted to find out their preference for drug information sources. Methods: The present study was prospective, observational, questionnaire-based survey. The study was conducted between March 2017 and April 2017. The study included postgraduate medical residents pursing speciality courses at a tertiary care teaching hospital in Navi-Mumbai. Data was compiled and analysed in Microsoft excel. Results: Majority postgraduate residents preferred Non-electronics source for drug information. Text books (84%) were commonly preferred followed by medical journals in Non-electronic sources while internet-websites (76%) followed by e-journals and e-books were preferred in electronic sources. Majority preferred non-electronic sources for drug pharmacology and adverse reactions while electronic was preferred for indication, interaction, cost and therapy guidelines. For information on new drugs, majority preferred journals (71%) and websites (64%). Lack of time, source knowledge and high cost were perceived limiting factors for drug information. Conclusions: Postgraduate residents have varied preferences for drug information resources. Internet websites poses a challenge for authentic drug information. Interventions in the form of continuous medical education are required to improve their information-seeking behaviours.